The value of early recognition of fetal lymphangioma - Farnaghi, Soheil (Australas J Ultrasound Med, 2015)
Introduction: Lymphangiomas are very rare benign tumors of the lymphatic system, appearing as uniseptate or multiseptate cystic masses, which are usually located in the cervical or axillary area. Postnatal outcome depends on the size and location of the lesion. An increasing number of such congenital abnormalities are detected on routine conventional prenatal ultrasonography. Although prenatal evaluation for the prognosis of fetal lymphangioma has been based on two‐dimensional ultrasonography, magnetic resonance imaging may help in assessing the extent of a lesion. Isolated lymphangiomas generally have a favourable prognosis and sclerotherapy or surgical resection is effective in most of the cases. Case presentation: We present two cases of fetal axillary lymphangioma. In the first case, the lymphangioma was diagnosed antenatally, so parents were comprehensively counselled and post natal follow up was organised at a tertiary hospital. The second case remained undiagnosed until birth. This caused significant distress to both the parents and clinicians, especially after a coincident traumatic delivery. Conclusion: Both these cases emphasise that early diagnosis of fetal lymphangioma is critical and a combination of ultrasonography and magnetic resonance imaging can facilitate detection of lesions which are relatively limited and accessible to therapy in utero. This would also enable clinicians to perform a karyotype and comprehensively consult parents regarding the treatment and delivery options as well as outcome of the pregnancy.